The Structuring Role of Rhodolith Beds on Meiobenthic Communities in the Mediterranean Sea - Cocozza di Montanara, Adele; Semprucci, Federica; Rendina, Francesco; Russo, Giovanni Fulvio; Sandulli, Roberto (Aquatic conservation, 2025)
ABSTRACT Rhodolith beds are globally distributed structurally complex habitats formed by the aggregation of unattached forms of non‐geniculate coralline red algae. They provide key ecosystem functions and services, supporting feeding, settlement and nursery provision for several species. Despite their importance, the associated faunal biodiversity is poorly known, particularly with regard to meiofauna. The Mediterranean is particularly lacking in data; here, meiofaunal samples were collected in three sites from the Tyrrhenian Sea (Italy) aiming to characterize for the first time the meiofaunal communities associated with mesophotic rhodolith beds, exploring whether the microhabitat structure of rhodoliths influences variations in meiofaunal composition compared to the underlying sediment microhabitat. A total of 17 taxa was recorded. A high level of dissimilarity was found between the two different microhabitat types (i.e., rhodoliths and sediments), suggesting that meiofauna is more influenced by ‘micro’ than ‘macro’ spatial scale from both a qualitative and quantitative point of view. Rhodoliths showed a distinct meiofauna represented by copepods and many representative taxa of temporary meiofauna (macrofaunal juveniles), supporting the nursery role of rhodoliths. Conversely, sediments were mainly composed of sediment‐dwelling organisms (nematodes and platyhelminthes). The presence of such a multifaceted meiobenthic community, especially in more structurally complex rhodoliths, might favour the resilience of the system and recovery processes after environmental perturbations. These findings underline the key role of rhodoliths as habitat formers and biodiversity/stability enhancers in coastal ecosystems.